The Causal Links between Economic Growth, Renewable Energy, Financial Development and Foreign Trade in Gulf Cooperation Council Countries - Ben Hassine, Mustapha; Harrathi, Nizar (International Journal of Energy Economics and Policy, 2017)
This paper examines the causal relationship between renewable energy consumption, real GDP, trade and financial development for the GCC countries during the period 1980-2012. Compared to the previous studies, our models are extended by including the financial development as macroeconomic factor. The results indicate bidirectional causality in both short and long-run between output and exports. While, there is no evidence of causality in the short-run between output and renewable energy consumption or private sector credit and between exports and renewable energy consumption or private sector credit. Moreover, the long-run estimated results indicate that there is evidence of a statistically significant impact of renewable energy consumption, exports and private sector credit on output. Our finding indicates that renewable energy use and exports are able to increase the economic growth for the GCC countries. Nevertheless, we find negative impact of the financial development on economic growth related to the deflationary monetary policy of the considered countries. Keywords: Granger Causality, Panel Cointegration, Renewable Energy Consumption, Economic Growth, Financial Development; Trade; GCC Countries JEL Classifications: C33; O24; Q43